Adaptation of soil microbial growth to temperature: Using a tropical elevation gradient to predict future changes. (6th January 2019) - Nottingham, Andrew T.; Bååth, Erland; Reischke, Stephanie; Salinas, Norma; Meir, Patrick
Abstract: Terrestrial biogeochemical feedbacks to the climate are strongly modulated by the temperature response of soil microorganisms. Tropical forests, in particular, exert a major influence on global climate because they are the most productive terrestrial ecosystem. We used an elevation gradient across tropical forest in the Andes (a gradient of 20°C mean annual temperature, MAT), to test whether soil bacterial and fungal community growth responses are adapted to long‐term temperature differences. We evaluated the temperature dependency of soil bacterial and fungal growth using the leucine‐ and acetate‐incorporation methods, respectively, and determined indices for the temperature response of growth: Q 10 (temperature sensitivity over a given 10oC range) and T min (the minimum temperature for growth). For both bacterial and fungal communities, increased MAT (decreased elevation) resulted in increases in Q 10 and T min of growth. Across a MAT range from 6°C to 26°C, the Q 10 and T min varied for bacterial growth ( Q 10–20 = 2.4 to 3.5; T min = −8°C to −1.5°C) and fungal growth ( Q 10–20 = 2.6 to 3.6; T min = −6°C to −1°C). Thus, bacteria and fungi did not differ significantly in their growth temperature responses with changes in MAT. Our findings indicate that across natural temperature gradients, each increase in MAT by 1°C results in increases in T min of microbial growth by approximately 0.3°C and Q 10–20 by 0.05, consistent with long‐term temperature adaptation of soil microbial communities. A 2°C warming would increase microbial activity across a MAT gradient of 6°C to 26°C by 28% to 15%, respectively, and temperature adaptation of microbial communities would further increase activity by 1.2% to 0.3%. The impact of warming on microbial activity, and the related impact on soil carbon cycling, is thus greater in regions with lower MAT. These results can be used to predict future changes in the temperature response of microbial activity over different levels of warming and over large temperature ranges, extending to tropical regions. Abstract : We show that soil microbial community growth is adapted to temperature along a 3.5 km elevation gradient in the Andes. Here, the temperature sensitivity of bacterial growth (A) is expressed by T min as affected by mean annual temperature (MAT). We use our findings to predict the temperature sensitivity of microbial activity to a warming of 2°C and to predict how temperature adaptation of growth would moderate this response (B). These results can be used to predict future changes in the temperature response of soil microbial activity over different levels of warming and over large temperature ranges, extending to tropical regions.